Research on Legal Issues of Homestead Use Right Inheritance - Yuxin Ma (Studies in Law and Justice, 2023)
The right to use the homestead of the attached house should be inheritable property. For both living function and identity attribute of welfare housing land use right and the property of the legal heir properties, solution to inherit the land use right and a home a home of the law and the conflicts in the provinces, autonomous regions and municipalities directly under the central area of the standard question, successor when inheritance regardless of whether it is the collective economic organizations are members adhere to the housing land use right of the building, after inheritance, if the non-members of the collective economic organization do not live in the house for a period of time or a family with multiple houses does not meet the stipulated standard area of one of the two cases of “exceptional restriction”, they shall be charged a fee and converted into the right to use or lease of collective business construction land, and the income from the conversion of rights shall be stipulated in a corresponding proportion to give the successor compensation to moderately revitalize the homestead system. To reduce the actual situation of idle house land.